Comparative efficacy of oral and vaginal probiotics in reducing the recurrence of bacterial vaginosis: a double-blind clinical trial - Mahnaz Boroumand Rezazadeh; Minoo Zanganeh; Lida Jarahi; Zahra Fatehi (BMC, 2024)
Abstract Objective The primary goal of this study is to discern the optimal adjuvant treatment for patients diagnosed with bacterial vaginosis, focusing on reducing recurrence rates. Methods This study is a double-blind clinical trial with no previous similar trials conducted to date. The study population consisted of non-pregnant, married women visiting teaching hospitals' clinics in Mashhad, complaining of vaginal discharge. After informed consent and questionnaire completion, samples were obtained from vaginal discharge surrounding the cervix of clinically diagnosed bacterial vaginosis patients. Using Gram staining, a gold standard method for bacterial vaginosis diagnosis, samples were examined under a microscope according to the Nugent score. After initial treatment with metronidazole, patients were divided into two groups receiving either vaginal or oral probiotics. Results Of the 55 participating women, 20 were in the vaginal probiotic group and 35 were in the oral probiotic group. No significant demographic or clinical differences existed between groups at baseline. The Nugent score decreased from 8.5 to 3 in the vaginal group and from 9 to 3 in the oral group, suggesting the effectiveness of both treatments. While the difference between groups was not statistically significant, each group showed significant improvements from their initial states (p-value < 0.001). Conclusion No significant difference was observed in the effectiveness of oral versus vaginal probiotics in reducing the recurrence of bacterial vaginosis after routine treatment. Therefore, the type of probiotic to be used could be chosen based on patient preference.